To solve the inequality, we can simplify both sides and then isolate the variable t.
3t ≥ 10 - 5(t + 7) - 1
First, distribute the -5 to the expression (t + 7):
3t ≥ 10 - 5t - 35 - 1
Simplify the expression on the right side:
3t ≥ -5t - 26
Next, add 5t to both sides to get the variable term on one side:
3t + 5t ≥ -26
Combining like terms:
8t ≥ -26
Finally, divide both sides by 8 to isolate the variable t:
t ≥ -26/8
Simplifying the fraction:
t ≥ -13/4
So the solution to the inequality is t ≥ -13/4.
Solve the inequality 3t≥10−5(t+7)−1
.
1 answer